The Effect of Blended Learning on Crisis Management During the Corona Pandemic (COVID-19 ) - Allah Yousif Alwan*, Azat; Abdullah Mohammed, Atheer (Journal of Economics and Administrative Sciences, 2024)
This research endeavors to investigate the influence of blended learning on the effective management of the educational challenges posed by the COVID-19 pandemic within nine government and private colleges in Iraq, to assess the level of interest exhibited by these institutions in the principal research variables and their dimensions. Additionally, the research seeks to formulate a set of conclusions aimed at enhancing performance standards to ensure the attainment of quality outcomes. These conclusions are founded upon the novelty and pressing significance of these variables in sustaining the educational process. The research methodology adopted for this research is primarily descriptive and analytical. The research population comprises teachers affiliated with departments specializing in administrative and economic sciences across the selected colleges, with a total sample size of 142 teachers. The principal research instrument employed is a questionnaire distributed to the aforementioned teachers. Furthermore, the research harnesses SPSS V.26 statistical software, for the analysis of the primary data. Both descriptive and inferential statistical techniques are utilized to assess and validate the research hypotheses. The statistical analysis reveals several noteworthy findings, most notably a substantial correlation and impact of blended learning across its dimensions (infrastructure suitability, teacher readiness, student readiness, and curriculum suitability) in the realm of crisis management, encompassing various dimensions ) the detection of warning signals, preparedness and prevention, damage containment, activity restoration, and learning(. Paper Type: Research paper